LncRNA NNT-AS1/hsa-miR-485–5p/HSP90 axis in-silico and clinical prospect correlated-to histologic grades-based CRC stratification: A step toward ncRNA Precision - El-Sheikh, Nada M.; Abulsoud, Ahmed I.; Fawzy, Amal; Wasfey, Eman F.; Hamdy, Nadia M. (Pathology, research and practice, 2023)
The oncogenic effects of long non-coding RNA (lncRNA) Nicotinamide Nucleotide Transhydrogenase-antisense RNA1 (NNT-AS1) role in colorectal cancer (CRC) hasn’t been sufficiently inspected in relation to the Homo sapiens (hsa)-microRNA (miR)− 485–5p/ heat shock protein 90 (HSP90) axis, clinically. qRT-PCR was performed to detect lncRNA NNT-AS1 and hsa-miR-485–5p expression levels in 60 Egyptian patients' sera. HSP90 serum level was quantified using Enzyme-linked immunosorbent assay (ELISA). The relative expression level of the studied non-coding RNAs as well as the HSP90 ELISA concentration were correlated with patients clinicopathological characteristics and correlated to each other. The axis diagnostic utility in comparison with carbohydrate antigen 19–9 (CA19–9) and carcinoembryonic antigen (CEA) tumor markers (TMs) was studied by receiver operating characteristic (ROC) curve analysis. The relative lncRNA NNT-AS1 expression level fold change 56.7 (13.5–112) and HSP90 protein ELISA level 6.68 (5.14–8.77) (ng/mL) were elevated, while, for hsa-miR-485–5p 0.0474 (0.0236–0.135) expression fold change was repressed in CRC Egyptian patients’ cohort sera, being compared to 28 apparently healthy control subjects. LncRNA NNT-AS1 specificity is 96.4% and a sensitivity of 91.7%, hsa-miR-485–5p showed 96.4% specificity, 90% sensitivity, and for HSP90 89.3%, 70% specificity and sensitivity, respectively. Those specificities and sensitivities were superior to the classical CRC TMs. A significant negative correlation was found between hsa-miR-485–5p with lncRNA NNT-AS1 (r = −0.933) expression fold change or with HSP90 protein blood level (r = −0.997), but, significant positive correlation was there between lncRNA NNT-AS1 and HSP90 (r = 0.927). LncRNA NNT-AS1/hsa-miR-485–5p/HSP90 axis could be a prospect for CRC development as well as diagnosis. Being correlated and related to CRC histologic grades 1–3, therefore, lncRNA NNT-AS1/hsa-miR-485–5p/HSP90 axis (not individually) expression approved clinically and in silico, could aid treatment precision. [Display omitted]